Microplastic Contamination in Marine Fish and Shells in the Coastal Areas of Jember Regency, Indonesia - Prehatin Trirahayu Ningrum; Abul Haris Suryo Negoro; Didin Erma Indahyani; Kusnadi; Yanuar Nurdiansyah (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research Fish and shellfish on the coast of Payangan and Puger Several types of microplastics were detected in their gastrointestinal tract There were microplastic types of fiber, fragments, granules, and filaments Abstract Every year, it is estimated that the Indonesian seas receive 100,000-400,000 tons of plastic waste used for human consumption. Indiscriminate disposal of plastic waste will have an impact in the future. The problem of microplastics is an illustration that the use of plastic in daily activities will cause environmental ecological damage. The purpose of the study was to describe microplastic contamination in marine fish and shells in the coastal areas of Jember Regency, Indonesia. The method used is to detect and identify the type and numbers of microplastic particles in the gastrointestinal tract content of sea fish and shells obtained from fishermen around Payangan and Puger coastal Jember, Indonesia. The gastrointestinal tract was extracted with peroxide oxidation method (WPO). A light microscope was used to examine microplastic particles of types and numbers. The results showed that marine fish and shells in the coastal area of Jember Regency, Indonesia have been contaminated with microplastic. The microplastic in each marine fish and shells sample has a different type. There were microplastic types of fiber, fragments, granules, and filaments in the shells sample, while in the marine fish samples, there were all these types except granules. Fish and shellfish on the coast of Payangan and Puger had several types of microplastics detected in their gastrointestinal tract.